(untitled) - Islam, Kaliym A. (San Francisco, 2007)
This book introduces not only a great media, but a great approach for developing and deploying podcasts in a training environment. Podcasting 101 for Training and Development is a must read for any training manager who must deploy frequently changing training programs to a distributed workforce
Keywords: Employees,Educational technology,Nhân viên,Công nghệ giáo dục; Training of,Đào tạo